A Brief Exploration of Audience, Flow and Fabrication in Three School Exercise Books from 1955, 1986 and 2016. Issue 3 (3rd July 2018) - Morley, Colin
ABSTRACT: The exercise book has been a ubiquitous piece of school equipment since the advent of mass literacy. This case study explores three teenage boys' exercise books, my father's, mine and a Year 9 in my current school. One each from 1955, 1986 and 2016. It explores how the boys' writing within them was shaped and constructed, for what audience and for whose benefit. Pages are looked at both for the writings of the boys and the comments of their teachers, and the dialogue that is occasionally shown is commented upon and conclusions drawn. Within the exploration of these books the case study also focuses on the changing form and function of the exercise book. It analyses how the performativity agenda prevalent within secondary schools in England has altered both the appearance and function of the exercise book. It concludes by commenting on how the demand for scrutinisable assessment policies have changed the function of these books from being a document of practice and process between student and teacher to one which is a display of fabricated compliance for external scrutiny.